Critical path identification in tuna export supply chain using Program Evaluation and Review Technique (PERT): A case study in Aceh, Indonesia - Friesca Erwan; Shaumy Fadhilla; Prima Denny Sentia; Rizky Agam Syahputra (Journal Industrial Servicess, 2026)
Tuna is one of the leading commodities in Aceh's coastal areas and has considerable export potential. However, managing the tuna export supply chain from Aceh to Jakarta involves several challenges, particularly delivery delays and extended processing lead times. To address these issues, this study applies the Program Evaluation and Review Technique (PERT) to identify and analyze the critical path activities within the tuna supply chain. The analysis was conducted based on actual data covering a complete supply chain cycle, including raw tuna procurement, processing, and distribution to Jakarta. The PERT evaluation estimated the total duration of one cycle to be approximately 22,684.297 minutes, equivalent to 15.75 days. The critical path requiring special attention comprises supplier operations at Laweung Port in Aceh, the CO treatment process in the processing facility, and transportation from Bakauheni Port to the forwarding company in Jakarta. This study recommends that tuna processing companies strengthen collaboration among all stakeholders to reduce critical path delays, enhance value-added activities, and maintain tuna stock quality throughout the supply chain.